Microbial functional metabolism drives the effects of exogenous additives on carbon storage and degradation during aerobic composting - Li, Mingxiu; Duan, Manli; Qin, Zhenlun; Zhou, Beibei; Wang, Quanjiu; Xu, Hongbo; Weng, Haiyong (Frontiers in Environmental Science, 2024)
This study conducted composting experiments using cow manure and wheat straw, employing five different treatment methods (CK, magnetized water treatment-M, magnetized water combined with biochar treatment-SM, magnetized water combined with ferrous sulfate treatment-FM, magnetized water combined with Bacillus megaterium treatment-GM), aiming to accelerate the composting maturation process and reduce carbon loss. The results of the experiments showed that the SM treatment entered the thermophilic phase on the 2nd day and lasted for 9 days, resulting in the best maturation effect. The FM treatment increased the carbon content in the compost, effectively preserving carbon sources. PCA analysis revealed significant differences in microbial community structures due to different treatments. Additionally, SEM observations indicated that different treatments affected the compost environment, thereby influencing microbial activity and carbon content. Overall, the SM treatment positively affected the compost maturation process, while the FM treatment effectively preserved carbon sources in the compost.